Modelling of runway excursions using Fault Tree Analysis - Sekulić Jovana M. (Savez inženjera i tehničara Srbije, 2021)
Runway excursion (RE) is recognized as one of the main Airport Safety Issues. It can be defined as an event in which an aircraft veers-off or overruns the runway surface during either takeoff or landing. In this paper an application of Fault Tree Analysis (FTA) method on RE events is presented. FTA belongs to quantitative class of causal methods. It estimates the risk of incident or accident according to estimation of probability of occurrence of each cause of an event. It might be restricted to pure statistical analysis based on the available data or combine these data with expert judgment on the accident causes. The aim of this paper is to identify potential causal factors. In order to illustrate FTA application on RE, two models were developed: one for landing and other for take-off. Application of FTA has shown what are the most critical causal factors whose knowledge allows developing certain measures to reduce the risk of RE.